2006
DOI: 10.3989/scimar.2006.70n4709
|View full text |Cite
|
Sign up to set email alerts
|

Interpopulational differences in the female reproductive cycle of the southwestern Atlantic estuarine crab <i>Chasmagnathus granulatus Dana</i>, 1851 (Brachyura: Grapsoidea: Varunidae)

Abstract: SUMMARY:The female reproductive biology of Chasmagnathus granulatus Dana, a semiterrestrial burrowing crab endemic to the southwestern Atlantic, was compared in two contrasting coastal habitats: San Antonio (SA, marine) and Mar Chiquita (MC, estuarial). Mature females were collected monthly for 1.5 years and the ovarian cycle was described using a qualitative scale. Gonadosomatic (GSI) and hepatosomatic (HSI) indexes were calculated. The highest GSI and HSI occurred early in the reproductive season in SA and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 39 publications
0
35
0
2
Order By: Relevance
“…Although the percentage of ovigerous females over the year is the most common technique used to determine the reproductive period of a species (HEMNI & KANETO 1989), the go- (RUFFINO et al 1994, LÓPEZ-GRECO & RODRÍGUEZ 1999, ITUARTE et al 2004. High percentages of females with advanced gonadal development throughout the year indicate that they have good nutrition, suggesting a highly productive environment which supplies nourishment to the crabs.…”
Section: 5mentioning
confidence: 99%
“…Although the percentage of ovigerous females over the year is the most common technique used to determine the reproductive period of a species (HEMNI & KANETO 1989), the go- (RUFFINO et al 1994, LÓPEZ-GRECO & RODRÍGUEZ 1999, ITUARTE et al 2004. High percentages of females with advanced gonadal development throughout the year indicate that they have good nutrition, suggesting a highly productive environment which supplies nourishment to the crabs.…”
Section: 5mentioning
confidence: 99%
“…Dense populations of this species are found in estuarine mudXats and salt marshes, as well as in coastal bays and lagoons with highly variable salinities, temperatures, and tidal patterns (Spivak 1997). Studies of diVerent populations of this species have shown diVerences, particularly between marine and estuarine habitats, in maximum adult body size, egg size, and in the timing and duration of the reproductive season (see Botto and Irigoyen 1979;D'Incao et al 1992;Anger et al 1994;RuVino et al 1994;Spivak et al 1994Spivak et al , 1996Iribarne et al 1997;Luppi et al 1997Luppi et al , 2002López-Greco and Rodríguez 1999;Ituarte et al 2004;Bas et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Intraspecific variation of life-history trades may be the consequence of regionally varying environmental conditions, and factors such as salinity, photoperiod, and food availability may be responsible for interpopulational variability in the reproductive biology of decapods (Kyomo 2000;Ituarte et al 2006;Bas et al 2007;Silva et al 2009). …”
Section: Introductionmentioning
confidence: 99%